The Synergy of Teachers and Parents through the Utilization of Online Learning Technology in Class II MI NU Miftahul Tholibin Kudus: Sinergitas Antara Guru Dengan Orang Tua Melalui Pemanfaatan Teknologi Pembelajaran Daring Pada Kelas II MI NU Miftahut Tholibin Kudus - Anni Qurrotul Aini; Elya Umi Hanik (Jurnal Teknologi Pembelajaran, 2021)
Learning that is carried out online requires students to learn independently. Some students are not on time and even forget to take part in online learning which is done online. The beginning of online learning makes students lag behind in lessons so they don't understand the lesson. For that, it is necessary to build synergy between teachers and parents of students in order to realize the success of online learning. This study aims to determine how communication between teachers and parents in achieving learning achievement during the Covid-19 pandemic through the use of learning technology and to determine the extent of student learning outcomes in online learning using current learning technology. In this study using qualitative research methods. This type of qualitative research used by researchers is in the field. Communication between teachers and parents of class II MI NU Miftahut Tholibin Kudus during the Covid-19 pandemic was carried out via smartphones on the Whatsapp application. Through WhatsApp private chat, teachers can ask questions about students' cognitive development. Likewise, parents and teachers can ask questions about teaching materials that have not been understood so far. Meanwhile, student skills can be seen by the teacher via video call or zoom. Student learning outcomes during online learning are less satisfying than normal learning.